Development of Neuronal Guidance Fibers for Stimulating Electrodes: Basic Construction and Delivery of a Growth Factor - Wille, Inga; Harre, Jennifer; Oehmichen, Sarah; Lindemann, Maren; Menzel, Henning; Ehlert, Nina; Lenarz, Thomas; Warnecke, Athanasia; Behrens, Peter (Frontiers in Bioengineering and Biotechnology, 2022)
State-of-the-art treatment for sensorineural hearing loss is based on electrical stimulation of residual spiral ganglion neurons (SGNs) with cochlear implants (CIs). Due to the anatomical gap between the electrode contacts of the CI and the residual afferent fibers of the SGNs, spatial spreading of the stimulation signal hampers focused neuronal stimulation. Also, the efficiency of a CI is limited because SGNs degenerate over time due to loss of trophic support. A promising option to close the anatomical gap is to install fibers as artificial nerve guidance structures on the surface of the implant and install on these fibers drug delivery systems releasing neuroprotective agents. Here, we describe the first steps in this direction. In the present study, suture yarns made of biodegradable polymers (polyglycolide/poly-ε-caprolactone) serve as the basic fiber material. In addition to the unmodified fiber, also fibers modified with amine groups were employed. Cell culture investigations with NIH 3T3 fibroblasts attested good cytocompatibility to both types of fibers. The fibers were then coated with the extracellular matrix component heparan sulfate (HS) as a biomimetic of the extracellular matrix. HS is known to bind, stabilize, modulate, and sustainably release growth factors. Here, we loaded the HS-carrying fibers with the brain-derived neurotrophic factor (BDNF) which is known to act neuroprotectively. Release of this neurotrophic factor from the fibers was followed over a period of 110 days. Cell culture investigations with spiral ganglion cells, using the supernatants from the release studies, showed that the BDNF delivered from the fibers drastically increased the survival rate of SGNs in vitro. Thus, biodegradable polymer fibers with attached HS and loaded with BDNF are suitable for the protection and support of SGNs. Moreover, they present a promising base material for the further development towards a future neuronal guiding scaffold.